Pengaruh Media Swim-up terhadap Karakteristik Spermatozoa Epididimis Kerbau: Sperma kerbau - Rini Elisia; Maiyontoni (Program Studi peternakan, 2022)
The objective this study was to improve the best of swim-up media for buffalo epididymal spermatozoa used embryos produce by in vitro fertilization. Epididymal sperm collected from buffalo examined macroscopically and microscopically. Three media were used for the swim-up sperm: TALP, mBO and TCM-199. The results epididmys buffalo sperm motility percentage indicates that more influenced significantly (P<0,05) on all three swim-up media with TALP averaging 74,17 ± 7,35; mB-O 77,5 ± 4,03; TCM-199 67,5 ± 5,15. For buffalo epididymal spermatozoa percentage was also influential shows significant (P<0,05) on the three swim-up media with TALP averaging 90,76 ± 4,04; mB-O 91,86 ± 4,63; TCM-199 80,73 ± 9,6. While the percentage TAU of buffalo epididymal spermatozoa showed that no significant effect (P>0,05) in the three swim-up media with TALP averaging 81,36 ± 5,38; medium BO 80,22 ± 6,35; TCM-199 79,62 ± 7,69. From these results it can be concluded that the use of media medium BO is able to maintain the characteristics of buffalo epididymal spermatozoa in vitro better than the other two media.